Weight categories do not prevent athletes from Relative Age Effect: an analysis of Olympic Games wrestlers - Rodrigues Albuquerque, M.; Teoldo da Costa, V.; Oliveira Faria, L.; Calábria Lopes, M.; Menezes Lage, G.; Sledziewski, D.; Szmuchrowski, L. A.; Franchini, E. (Archives of Budo, 2014)
Background and Study Aim: Relative Age Effects (RAE) refer to the effects of age differences among individuals who have been grouped together. This study aimed is knowledge about RAE in Olympic Games wrestlers to analyse its effects on all athletes, styles, and medallists, considering males and females separately. Material and Methods: The names and birthdates of the Olympic wrestlers were collected from open-access websites. In this study, we analysed male and female competitors separately. Results: The main results of this investigation were the presence of RAE in all styles, freestyle medallists, and freestyle main medalling countries, only in male athletes. Conclusions: Thus, in a selected group of wrestlers who had participated at the highest competitive level, RAE were in all styles, only in male athletes. In addition, our data suggest that RAE cannot be eliminate only by weight categories.